Automatic generation of XML-based editors for autonomic systems. (7th May 2010) - Barbar, Kablan
Nowadays, autonomic systems are emerging as a promising computing approach which manages itself without external interactions in the case of context changing. Several works have dealt with the design and implementation of autonomic systems. However, few approaches pay attention to the autonomic behaviour of data-entry forms or graphical interfaces in autonomic architecture. In this work, we will introduce a generic autonomic system that is based on context and data-entry devices and generates DTDs which describe the relevant context and data-entries. We propose a DTD compiler based on attributed context-free grammar which automatically generates web forms or editors to capture data with respect to the predefined DTD. This contribution introduces a high-level grammar that supports all possible DTD interpretation by other languages like VB or Ajax or Java.